(untitled) (Journal of Pathology of Nepal, 2023)
Urachal carcinoma is a rare and aggressive cancer arising from a persistent urachus which is a remnant of the allantois that extends from blader to umblicus.This is a case report of urachal carcinoma in a 37 year old male who presented with gross painless hematuria . On radiological investigation he was found to have a tumor involving dome of bladder and urachal remnant. Cystoscoic biopsy suggested carcinoma. Partial cystectomy with enblock removal of urachus and umblicus was done. On cutting the specimen through umblicus the urachal remnant was identified very well with a tumor from distal urachus infiltrating into the bladder. Histologicaly this tumor was identified as adenocarcinoma-enteric type involving, urachus , bladder and perivesical fat.